Désir de multitude. Différence, antagonisme et politique matérialiste - Aragüés Estragués, Juan Manuel (Dissidences / Disidenci@s, 2021)
How can we develop a politics of difference with an antagonistic and materialist vocation? This is the big question that runs through this book. It is a question that, for the author, cannot be avoided by an ontological, anthropological and epistemological questioning, and which requires, above all, a relentless critique of the dominant philosophical line of Western thought. For one of the main obstacles to the implementation of an antagonistic policy could well be the persistence, in our modes of thought and organisation, of an idealistic conceptual arsenal that is incompatible with a materialist approach to reality. Idealism, from its Platonic origins, has thus constantly sought to erase the traces of difference that run through reality, and to ignore, or stifle, any discourse aimed at apprehending reality under the prism of the most radical immanence. However, there is a powerful materialist tradition, subterranean in its Milsian origins, which develops particularly from the writings of Spinoza, Marx and Nietzsche, opening the way to an important line of thought on the politics of difference of which Deleuze, Negri, or the Invisible Committee were, and still are, the main representatives. A line of thought that allows us to question in a new way the essentialist anchoring of entire sections of twentieth-century critical thought, in order to finally make difference the starting point of a materialist politics that, as Deleuze wrote, "is capable of changing everything".